2021
DOI: 10.1021/acs.jctc.1c00075
|View full text |Cite
|
Sign up to set email alerts
|

Kirkwood–Buff-Derived Force Field for Peptides and Proteins: Philosophy and Development of KBFF20

Abstract: A new classical nonpolarizable force field, KBFF20, for the simulation of peptides and proteins is presented. The force field relies heavily on the use of Kirkwood−Buff theory to provide a comparison of simulated and experimental Kirkwood−Buff integrals for solutes containing the functional groups common in proteins, thus ensuring intermolecular interactions that provide a good balance between the peptide−peptide, peptide−solvent, and solvent−solvent distributions observed in solution mixtures. In this way, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 234 publications
1
35
0
Order By: Relevance
“…32 This would be consistent with our Gly Ramachandran maps being too biased to the α region. However, as noted previously, 1 Pappu has suggested that these peptides were studied under high enough concentration that effects due to Correlation between experimental and simulated J-coupling constants for small peptides. The letters refer to the coupling type/angle using the following classification: a is 3…”
Section: ■ Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…32 This would be consistent with our Gly Ramachandran maps being too biased to the α region. However, as noted previously, 1 Pappu has suggested that these peptides were studied under high enough concentration that effects due to Correlation between experimental and simulated J-coupling constants for small peptides. The letters refer to the coupling type/angle using the following classification: a is 3…”
Section: ■ Resultsmentioning
confidence: 82%
“…In the first of this two-part study, we reported the philosophy behind, and subsequent development of, a Kirkwood−Buffderived force field (FF), KBFF20, for the simulation of peptides and proteins. 1 Here, we present results for the simulation of a variety of peptide and protein systems using KBFF20 and compare them to a variety of experimental data sets. In addition, we also provide some perspective for how well these results are compared to those of alternative early and modern class I FFs for the simulation of biomolecules in explicit solvent.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their efforts have focused on adjusting charge parameters, along with some LJ parameters, to match Kirkwood-Buff integral values and better capture solute-solvent interactions. This method has been used to parameterize a wide range of systems, from simple systems [35] to a complete protein and peptide force field [38].…”
Section: Introductionmentioning
confidence: 99%